2007
DOI: 10.1007/s00404-007-0384-7
|View full text |Cite
|
Sign up to set email alerts
|

The value of frozen sectioning for the evaluation of resection margins in cases of conization

Abstract: Frozen section examination can provide immediate and precise evaluation of the cone margin status in high-grade cervical intraepithelial neoplasia. It can identify frank invasion and permit adequate treatment in a one-stage procedure and reliably detect clear resection margins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…Furthermore, FSE accuracy rates of 93% (4) and 92% has been reported by others (8). Behtash et al (11) reported that the diagnosis by the FSE was in agreement with paraffin section in 26 out of 30 cases (87%), and paraffin section confirmed 3 invasive cases diagnosed intraoperatively. In addition, Hasanzadeh et al performed FSE on conization biopsy samples from 20 patients with highgrade CIN.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Furthermore, FSE accuracy rates of 93% (4) and 92% has been reported by others (8). Behtash et al (11) reported that the diagnosis by the FSE was in agreement with paraffin section in 26 out of 30 cases (87%), and paraffin section confirmed 3 invasive cases diagnosed intraoperatively. In addition, Hasanzadeh et al performed FSE on conization biopsy samples from 20 patients with highgrade CIN.…”
Section: Discussionmentioning
confidence: 76%
“…Following conservative CIN treatment, the two most undesirable conditions are the positive margins and the undiagnosed invasive disease. In these two situations, the treatment is considered incomplete and the risk of recurrence is very high (11).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of this approach have all been from academic centers in the United States [4, 7, 8] and other countries [5, 6, 9], and presumably pathologists at academic centers had extra training or interest in gynecologic malignancies. At MD Anderson Cancer Center, all specimens were reviewed by 1 of 6 pathologists subspecialized in the area of gynecologic pathology and therefore spend the majority of their time reviewing gynecology cases.…”
Section: Discussionmentioning
confidence: 99%
“…[4–9] However, these studies were limited to patients at single academic centers. The applicability of those findings to general practice remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Nur in Ausnahmefällen wird man ein Zervixbiopsat oder eine Konusspitze vom Pathologen im Schnellschnitt beurteilen lassen [23]. Der Kliniker weiß, dass die Aussagekraft über den Schweregrad der Läsion und die Resektionsgrenzen am im Paraffin eingebetteten Gewebe viel größer ist.…”
Section: Gebärmutterhalsunclassified